Response of Two Sunflower (Helianthus annuus L.) Genotypes to Foliar Application of Different Nano Fertilizers. - Abdalrazaq Bapir, Kazhya; Bahar Jalal Mahmood (Zanco Journal of Pure and Applied Sciences, 2022)
A field experiment was conducted at two locations in Sulaimanya governorate (Ranya and Saruchawa) during the autumn growing season of 2021 to investigate the effect of different sources of Nano fertilizer on the growth, yield, and quality of two sunflower genotypes. A factorial experiment was conducted using a randomized complete block design (RCBD) with three replicates which included sunflower genotypes (Velko and Baroloro) and Nano foliar fertilizer (Control, Nano Zn, Nano NPK, Super Nano, and Nano Fe). The statistical analysis indicated a significant effect of both factors and their interactions on most of the studied traits. The results indicated that the Velko genotype requires a shorter period for all growth stages, moreover recorded maximum seed yield (5.73 and 5.86) t ha-1 at both locations. On the other hand, the results showed that Super Nano fertilizer affected significantly most of the studied traits and obtained the highest value for leaf area (56.11and 61.72 cm2), leaf area index (1.23and 1.36), head diameter (11.76 and 13.55), head weight (191.23 and 245.21), seed index (70.05 and 72.29), seed yield (5.73 and5.86 ) t ha-1, and oil (37.76 and 38.60) % in addition to protein (19.83 and 23.40) %. at both locations respectively. The interaction treatment (Velko x Super Nano) recorded the highest value of oil and protein content (37.93, 38.61) % and (24.50, 24.25) %, on the other hand, the lowest values for most of the studied characters were recorded from Baroloro and Control treatment.